A Preliminary Assessment of Chonaikai and Banjar From the perspectives of the Comparative Sociology on the Community - Budiana, I Made; Otsuka, Ayami; Yoshihara, Naoki (Udayana Journal of Social Sciences and Humanities, 2019)
Today, with the advancement of globalization, it is essential to clarify how the local communities are changing from a viewpoint of comparative sociology, in order to evaluate the changes in the modern society from a broader point of view. This paper attempts to make a preliminary, comparative consideration between chonaikai in Japan and banjar in Bali. The results revealed the following: 1) local communities have always been placed in a top-down government framework through history; 2) yet, it demonstrates, from time to time in history, a dynamism rooted in the native social theory and customs; and 3) after all, local communities have reached a critical phase in the modern, post-colonial stage.